Peripheral Blood WT1 Expression Predicts Relapse in AML Patients Undergoing Allogeneic Stem Cell Transplantation. (17th August 2014) - Malagola, Michele; Skert, Cristina; Ruggeri, Giuseppina; Turra, Alessandro; Ribolla, Rossella; Cancelli, Valeria; Cattina, Federica; Alghisi, Elisa; Bernardi, Simona; Perucca, Simone; Di Palma, Andrea; Borlenghi, Erika; et al.
Abstract : To evaluate if WT1 expression may predict relapse after allo-SCT, we analyzed WT1 levels on peripheral blood (PB) and bone marrow (BM) before and after allo-SCT in 24 AML patients with WT1 overexpression at diagnosis. Five copies of WT1/ABL × 10 4 from PB were identified as the threshold value that correlated with relapse after allo-SCT. The same correlation was not identified when WT1 expression was assessed from bone marrow (BM). Eight out of 11 (73%) patients with a pre-allo-SCT PB-WT1 ≥ 5 and 4/13 (31%) patients with a pre-allo-SCT PB-WT1 < 5 relapsed, respectively ( P = 0.04). The incidence of relapse was higher in patients with PB-WT1 ≥ 5 measured after allo-SCT, at the 3rd (56% versus 38%; P = 0.43) and at the 6th month (71% versus 20%; P = 0.03). Patients with pretransplant PB-WT1 < 5 had significantly better 2-year OS and LFS than patients with a PB-WT1 ≥ 5 (81% versus 0% and 63% versus 20%) ( P = 0.02). Our data suggest the usefulness of WT1 monitoring from PB to predict the relapse in allotransplanted AML patients and to modulate the intensity of conditioning and/or the posttransplant immunosuppression in an attempt to reduce the posttransplant relapse risk.